2014
DOI: 10.1002/jbm.b.33265
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in single layer amnion allografts compared to multilayer amnion/chorion allografts for wound healing

Abstract: Human amniotic membrane allografts have proven effective at improving healing of cutaneous wounds. The mechanism of action for these therapeutic effects is poorly understood but is thought to involve the resident growth factors present in near term amniotic tissue. To determine the relative cytokine contribution of the amnion and chorion in amniotic allografts, the content of 18 cytokines involved in wound healing were measured in samples of PURION V R Processed dehydrated amnion, chorion, and amnion/chorion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 20 publications
3
87
2
Order By: Relevance
“…The proinflammatory cytokines TNF‐α, TNF‐β, and TGF‐β1 were not detected in the amnion. This finding is contrary to other existing literature, which demonstrated these cytokines present in amnion (Koob et al, ; Sane, Misra, Quintanar, Jones, & Mustafi, ). Because cytokine expression is multifaceted, this result may be due to a number of different factors such as the presence of chorion, varying processing techniques, and different structural organization of patches used in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…The proinflammatory cytokines TNF‐α, TNF‐β, and TGF‐β1 were not detected in the amnion. This finding is contrary to other existing literature, which demonstrated these cytokines present in amnion (Koob et al, ; Sane, Misra, Quintanar, Jones, & Mustafi, ). Because cytokine expression is multifaceted, this result may be due to a number of different factors such as the presence of chorion, varying processing techniques, and different structural organization of patches used in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…Clinical studies of placental membranes have demonstrated improved outcomes in a variety of wound types, including: acute wounds, DFUs, and venous leg ulcers . Placental tissues are processed in various ways, including: cryopreservation, hypothermic storage, and dehydration . Composition and processing alters the proteomic composition and may consequently affect how the grafts function …”
Section: Introductionmentioning
confidence: 99%
“…Placental tissues are processed in various ways, including: cryopreservation, hypothermic storage, and dehydration . Composition and processing alters the proteomic composition and may consequently affect how the grafts function …”
Section: Introductionmentioning
confidence: 99%
“…As there are limitations to every study, we acknowledge that our results may not be generalised to other amniotic membrane products seeing that scientific papers have been published describing differences among the products . It must also be recognised that all patients received a high level of care in a wound care centre.…”
Section: Discussionmentioning
confidence: 99%